PENGARUH BERMAIN TEBAK KATA TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK TITIPAN IBU PASIR EMAS KECAMATAN SINGINGI - Aflina, Yenike; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observations that have been made to the childâs speech is still not perfect and learning activities by teachers less appealing to children. It is therefore necessary given activity play charades. This study aims to determine the influence of playing hangman on speaking skills of children in kindergarten courier mother of the golden sand. The sample used in this study were 23 children. Technical analysis of the data used is the t-test using SPSS charades program 20. The hypothesis of this study is a significant difference between playing with the ability to speak kindergarten aged 5-6 years in TK Titipan Ibu Pasir Emas District Singingi.It is known from the analysis of data obtained = 15,724 and p = 0,000 for p < 0,05, it can be concluded Ha is received and a significant difference between playing charades with the childâs ability to speak, so it could mean that Ho is rejected and Ha accepted which means that there are significant differences between before and after use activity playing hangman on the ability to speak of children aged 5-6 years in kindergarten Titipan Ibu Pasir Emas that is by the amount of N gain = 20%.